Estimation of total antioxidant capacity from diet and supplements in US adults - Yang, Meng; Chung, Sang-Jin; Chung, Chin Eun; Kim, Dae-Ok; Song, Won O.; Koo, Sung I.; Chun, Ock K. (British journal of nutrition, 2011)
Given the importance of dietary antioxidants in reducing the risks of chronic diseases, the present study aimed to estimate the intake of total antioxidant capacity (TAC) from diet and dietary supplements of US adults. We utilised the US Department of Agriculture flavonoid and proanthocyanidin databases, dietary supplement data and food consumption data of 4391 US adults aged 19+ years in the National Health and Nutrition Examination Survey 2001–2. In order to convert the intake data of individual antioxidant compounds to TAC values, the vitamin C equivalent (VCE) of forty-three antioxidant nutrients measured previously was also applied. Daily TAC averaged 503·3 mg VCE/d (approximately 75 % from diet and 25 % from supplements). The energy-adjusted daily TAC level from diet and supplements was higher in women (except for carotenoids), older adults, Caucasian (except for carotenoids), non-alcohol consumers (for vitamin E and proanthocyanidins), subjects with higher income (except for carotenoids) and higher exercise levels than their counterparts (P < 0·05). TAC was positively associated with daily consumption of fruits and fruit juices, vegetables and vegetable products, beverages, wines and teas (P < 0·001). Teas, dietary supplements, and fruits and fruit juices were the major sources of dietary TAC of the US population (28, 25 and 17 %, respectively), while the contribution of vegetables and vegetable products to TAC was minimal ( < 2 %). The present study indicates that antioxidant intake from various diet and supplements contributes to TAC status. TAC levels are different in sociodemographic subgroups of the US population. The relationship between TAC intake and risks of chronic disease warrants further investigation.